2017
DOI: 10.1007/s10792-017-0479-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dehydration and fasting on intraocular pressure and corneal biomechanics measured by the Ocular Response Analyzer

Abstract: Our results reveal that fasting during Ramadan does not profoundly affect corneal biomechanics and IOP values in healthy volunteers without ocular diseases such as glaucoma. When planning corneal refractive surgery and determining IOP, the ORA measurements can be done safely during a Ramadan fast. Moreover, ORA may be a better alternative for patients that refuse IOP measurement via GAT for examining the accuracy of IOP during fasting. Further studies are needed to better understand the role of these parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…52 Uysal et al have demonstrated that fasting did not affect IOP and corneal biomechanics valueson a Caucasian population with glaucoma. 53 Reduction in water intake following aqueous humor formation may affect prostaglandin secretion and IOP reduction. Furthermore, alteration of α-adrenergic tone due to activation of sympathetic system may increase outflow resistance and subsequent IOP changes.…”
Section: Fastingmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Uysal et al have demonstrated that fasting did not affect IOP and corneal biomechanics valueson a Caucasian population with glaucoma. 53 Reduction in water intake following aqueous humor formation may affect prostaglandin secretion and IOP reduction. Furthermore, alteration of α-adrenergic tone due to activation of sympathetic system may increase outflow resistance and subsequent IOP changes.…”
Section: Fastingmentioning
confidence: 99%
“…Furthermore, alteration of α-adrenergic tone due to activation of sympathetic system may increase outflow resistance and subsequent IOP changes. 53 Though, further studies still need to determine mechanism of IOP changes in different ethnicities and confirm the exact mechanism of fasting.…”
Section: Fastingmentioning
confidence: 99%
“…The corneal resistance factor (CRF) captures the overall viscoelastic behavior of the cornea [10]. The correction of IOP according to CH could reduce the measurement of IOP by corneal factors, that is, Corneal-Compensated Intraocular Pressure (IOPcc) [11]. IOPcc is claimed to measure IOP independent of CCT and takes certain biomechanical properties of cornea into account.…”
Section: Introductionmentioning
confidence: 99%
“…The correction of IOP according to CH could reduce the measurement of IOP by corneal factors, that is, Corneal-Compensated Intraocular Pressure (IOPcc) [7,8] .…”
Section: Introductionmentioning
confidence: 99%